Online Teaching in K-12 Education in the United States: A Systematic Review - Johnson, Carla C.; Walton, Janet B.; Strickler, Lacey; Elliott, Jennifer Brammer (Review of Educational Research, 2022)
The transition to fully or partially online instruction for K?12 students necessitated by the 2020 COVID-19 pandemic highlighted the current lack of understanding of practices that support K?12 student learning in online settings in emergency situations but also, more troublingly, in K?12 online teaching and learning more generally. A systematic review of literature regarding K?12 online teaching and learning in the United States was therefore conducted to begin to fill this gap and to inform the work of policy makers, researchers, teacher educators, teachers, and administrators as they negotiate the changing role of online instruction in our nation?s educational systems. The review revealed a set of contextual conditions that are foundational to student learning in K?12 online settings (prepared educators, technology access and autonomy, students? developmental needs and abilities, and students? self-regulated learning skills). The literature also pointed to seven pillars of instructional practice that support student learning in these settings (evidence-based course organization and design, connected learners, accessibility, supportive learning environment, individualization, active learning, and real-time assessment).
Publisher: American Educational Research Association